Understanding Injury Patterns and Predictors in Pickleball Players: A Nationwide Study of 1,758 Participants - Oluwatoyosi B.A. Owoeye; Ted Yemm; Ryan Blechle; Mitchell Wayne; Dawn Kennedy; Wassim Mourad; Katie Stamatakis; Timothy Howell (Sports Medicine - Open)
Abstract Background Despite pickleball’s rapid growth in the United States, research regarding the patterns and predictors of injuries remain sparse. Objectives To describe the prevalence and characteristics of injuries, including time-loss (stopping play for at least a day) and non-time-loss injuries, and evaluate the predictors of injuries in pickleball players. Methods A cross-sectional study was conducted. Pickleball players ≥ 18 years of age across the United States, who participated in pickleball at least once a month, were invited to take a pre-validated survey. The primary outcome was self-reported all-complaint injuries, including any physical complaints in the past 12 months. Results A total of 1,758 participants (mean age: 62.7 ± 13.0 years) were included in the final analysis. The 12-month prevalence of all-complaint injuries was 68.5% (95% CI: 66.3–70.7%), with time-loss injuries at 40.8% (95% CI: 38.5–43.1%) and non-time-loss injuries at 51.2% (95% CI: 49.4–54.1%). The point prevalence of pain/ongoing injuries was 35.9% (95% CI: 33.1–38.7%). The knee reported the highest injury prevalence (29.1%) followed by combined lower extremity regions of thigh, leg and foot (26.9%), shoulder (22.2%), back (19.9%) and elbow (18.4%). The top “most serious” injury types were overuse/chronic conditions (35.3%), joint/ligament sprains (23.8%), and muscle strains/pulls (20.7%). Based on a multivariable logistic regression, significant predictors of injury included male sex (OR: 1.33, 95%CI: 1.07–1.65, p = 0.011), higher frequency of weekly play (OR: 1.45, 95%CI: 1.15–1.84, p = 0.002), fewer years (< 5 years) of play experience (OR: 1.50, 95%CI: 1.19–1.90, p = 0.001), low/moderate perception of injury prevention importance (OR: 2.02; 95%CI: 1.52–2.67, p < 0.001), and age categories ranging from 33 to 77 years (ORs ranging from 1.83 to 3.11, p ≤ 0.009). Neither increased duration of play nor higher body mass index significantly increased the odds of injury. Conclusions Injuries are common among pickleball players, with 69% experiencing at least one all-complaint injury annually, including two in five sustaining injuries that halt play and one in three continuing to play despite pain. These findings underscore the need for tailored injury prevention strategies to optimize the health benefits of pickleball. Identified predictors will inform future injury prevention initiatives in pickleball.